Otoritas Keagamaan Digital: Pembentukan Otoritas Islam Baru di Ruang Digital - Rahmat Hidayatullah (Ushuluna: Jurnal Ilmu Ushuluddin, 2024)
This study explores the formation process and characteristics of religious authority in digital spaces. Starting from the rise of “digital preachers” and “religious microcelebrities” in recent years, it examines how religious authority is constructed, imagined, and established within digital culture. Using a qualitative approach based on literature research, the study finds that digital religious authority is not shaped by external recognition of an individual’s connection to a foundational or prophetic past. Instead, it is driven by digital expertise, online visibility, and the prominence of content within an algorithm-driven reputation and ranking system. Digital religious authority results from ongoing labor to cultivate followers through aesthetics of persuasion and self-branding, enabling individuals to be perceived and recognized as charismatic figures based on algorithmic logic.